2011
DOI: 10.1093/cercor/bhr112
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Magnetic Stimulation Reveals Dissociable Mechanisms for Global Versus Selective Corticomotor Suppression Underlying the Stopping of Action

Abstract: Stopping an initiated response is an essential function, investigated in many studies with go/no-go and stop-signal paradigms. These standard tests require rapid action cancellation. This appears to be achieved by a suppression mechanism that has "global" effects on corticomotor excitability (i.e., affecting task-irrelevant muscles). By contrast, stopping action in everyday life may require selectivity (i.e., targeting a specific response tendency without affecting concurrent action). We hypothesized that whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
132
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(149 citation statements)
references
References 36 publications
13
132
4
Order By: Relevance
“…In particular, reactive inhibitory control seemed to have a "global" effect on corticomotor excitability (Cai, Oldenkamp, & Aron, 2012;Majid, Cai, George, Verbruggen, & Aron, 2012), whereas proactive inhibitory control was more selective (Majid, Cai, Corey-Bloom, & Aron, 2013). It has been suggested that reactive inhibitory control could be implemented via a hyperdirect pathway between the right IFG and the subthalamic nucleus (Aron et al, 2007), resulting in global inhibition (Majid et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, reactive inhibitory control seemed to have a "global" effect on corticomotor excitability (Cai, Oldenkamp, & Aron, 2012;Majid, Cai, George, Verbruggen, & Aron, 2012), whereas proactive inhibitory control was more selective (Majid, Cai, Corey-Bloom, & Aron, 2013). It has been suggested that reactive inhibitory control could be implemented via a hyperdirect pathway between the right IFG and the subthalamic nucleus (Aron et al, 2007), resulting in global inhibition (Majid et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Decreased excitability was found in task-irrelevant muscles during standard but not selective stopping (Majid et al, 2012). Additional event-related potentials (ERPs) were measured over frontal and parietal regions when stopping in contrast to when changing a motor response in a stop-change task; however these electrophysiological differences were accompanied by behavioural differences in stop or stop-change reaction time (Kramer et al, 2011).…”
Section: Introductionmentioning
confidence: 92%
“…As shown in the third row, only a global clearing of WM requires that all thought be cleared. In the motor domain, neural control mechanisms for global stopping, which is the cessation of all motor responding, are partially distinct from those required to stop a specific motor response (Aron & Verbruggen, 2008; Majid et al, 2012). Analogously, we predict that while some regions required for each of these distinct ways in which information is cleared from working memory will overlap, at least some will also be distinct.…”
Section: Introductionmentioning
confidence: 99%